Operation freak : narrative, identity, and the spectrum of bodily abilities - Flaugh, Christian, 1968- (McGill-Queen's University Press, 2012)
In Operation Freak, Christian Flaugh embarks upon an exploration of the intricate connection between the physical bodies and narratives that, subjected to all manner of operations, generate identity. The author spotlights such voluntary and involuntary acts to show how discourses of ability, disability, and bodily manipulation regularly influence the production in and of various Francophone texts. Flaugh's foundation is the critical examination of mutually-informing narratives: Francophone novels that hyperbolically signal normative discourses through quintessential "freaks" (monstres) such as the Siamese twin, the bearded lady, and the exotic witch; and the related sociocultural master narratives from North America, North Africa, and the Caribbean. Employing disability and freak culture theories alongside studies of identification and narrative, Flaugh's close readings move beyond polarized discussions of "disabled" and "non-disabled" bodies. They expand such discussions to articulate how ability - like identity and narrative - is impermanent. It passes and it is passed throughout a spectrum at the same time that it intersects regularly with various narratives of identity like citizenship, gender, and race. Each chapter reveals how "operation" is a profit-driven identification process informed by abilities and constantly reproduced by surgeons, slave masters, writers, and the "freak" protagonists themselves. An unflinching look at such manipulation, Operation Freak illustrates the undeniably visceral relation between bodily ability, identity, narrative, and normality carved onto the body of the freak of culture (monstre de la culture).